(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Abstract: Witness the current business environment changes rapidly reflected on the performance of the facility wishing to stay , which is no longer style reaction enough to handle installations with their environment , and quickly began to lose its luster with the emergence of a message and the vision of contemporary business environment from a set of parts interacting with each other and the concept of behavioral includes all dimensions of performance, it is imperative to adopt a system installations influence variables and positive interaction through the development of strategic plans and the use of implementation and follow-up strategies to ensure the effectiveness of the method for measuring performance. Therefore there was a need for contemporary techniques enables the business of measuring the physical assets and intangible knowledge and evaluate their performance Alostrteja. It will search a series of steps linking knowledge assets axis of learning and growth for balanced Score Card technology Bstratejaat businesses through maps strategy for measuring the descriptive as a concept by default integrated package of activities to help chart the way for the readiness of knowledge assets steps to verify the operational requirements and strategy for the businesses and for the parties affected by the way they work